E-OLC in a context of the Other: face, trace and cyberspace. (27th March 2008) - Lindberg, J. Ola; Olofsson, Anders D.
This paper starts with an investigation of the concept of community, various meanings and understandings that may be related to its use, and how community as a concept has been reconceptualised when being transferred from an offline to an online context. It continues by considering an understanding of 'Educational Online Learning Communities (E-OLC) in its context' as a question of being-together. Finally, it provides a discussion inspired by the thoughts of Emanuel Levinas, concluding that E-OLCs are conditioned in the unconditioned responsibility of being-for-the-other and that education and teaching, both on- and offline, becomes a question of taking the Other as the necessary condition for knowing oneself, and the responsibility for the Other becomes the first imperative as ethics becomes the first philosophy.